2014
DOI: 10.3109/07853890.2014.894286
|View full text |Cite
|
Sign up to set email alerts
|

Advice to follow a low-carbohydrate diet has a favourable impact on low-grade inflammation in type 2 diabetes compared with advice to follow a low-fat diet

Abstract: Background Inflammation may play an important role in type 2 diabetes. It has been proposed that dietary strategies can modulate inflammatory activity.Methods We investigated the effects of diet on inflammation in type 2 diabetes by comparing a traditional low-fat diet (LFD) with a low-carbohydrate diet (LCD). Patients with type 2 diabetes were randomized to follow either LFD aiming for 55–60 energy per cent (E%) from carbohydrates (n = 30) or LCD aiming for 20 E% from carbohydrates (n = 29). Plasma was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 37 publications
1
55
0
2
Order By: Relevance
“…Significant between‐group differences in HbA 1c were observed in six of the 25 RCTs . Some studies reported significant differences at 6 months which were not maintained at 12 months and beyond . Meta‐analyses conducted for HbA 1c for all studies found no overall effect of modifying carbohydrate and demonstrated a high level of heterogeneity [WMD –0.09% (95% CI –0.27, 0.08; P = 0.30); I 2 72% ( P <0.001); Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant between‐group differences in HbA 1c were observed in six of the 25 RCTs . Some studies reported significant differences at 6 months which were not maintained at 12 months and beyond . Meta‐analyses conducted for HbA 1c for all studies found no overall effect of modifying carbohydrate and demonstrated a high level of heterogeneity [WMD –0.09% (95% CI –0.27, 0.08; P = 0.30); I 2 72% ( P <0.001); Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Where separate baseline values are not reported, the entire cohort values are used for both groups. Additional data received directly from authors: Dyson, 2007 , Larsen, 2011 , Jonasson, 2014 , Ben‐Avraham, 2009 . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 1589 studies identified through database searches and cross reference list matching, 23 studies were included in the review (Figure ). The main reasons for exclusion were diet intervention not being low‐carbohydrate; duration of intervention being less than 3 months; study sample consisting of individuals without type 2 diabetes and studies using a non‐randomized and/ or non‐controlled trial design (Table S2).…”
Section: Resultsmentioning
confidence: 99%